PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMIK UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK TENTANG GETARAN MTS NEGERI 2 PONTIANAK - Siti Zulaiha; Haratua Tiur Maria; Syukran Mursyid (Universitas Tanjungpura, 2020)
Abstract This study aimed to identify and develop a comic-based learning media to improve student achievement about vibration subject. The method of this study was Research and Development (R&D) with the model of ADDIE (analysis, design, development, implementation, evaluation). The analysis stage was interviews with the teacher and class VIII J students of MTs Negeri 2 Pontianak, followed by the planning phase that comprised the process of designing the product. During the development phase, the media validation was tested before being implemented in class VIII J of MTs Negeri 2 Pontianak to determine the learning outcomes in the post-implementation phase. The product was then evaluated based on the eligibility data. Based on data analysis, the product is eligible to use based on the criteria: higher validity number; reliability of 0.770; the average score of pre-test > post-test by 41.11 > 77.78 with the difference value of 2.8; the responses on the product by 3.26 with the very good category; and, the effectiveness of product feasibility by 2.92 with a high classification. Therefore, the developed learning media is feasible and effective for improving the students’ achivemnt about vibration in class VIII J of MTs Negeri 2 Pontianak. Keywords: Learning Media, Comic, Vibration